Pembelajaran Berdiferensiasi Sebagai Upaya Menguatkan Profil Pelajar Pancasila Dalam Kurikulum Merdeka - I Wayan Agus Sukmadana; Ni Wayan Sudarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to describe the implementation of differentiation learning as an effort to strengthen the Pancasila Student Profile in the independent curriculum. This research is qualitative description research using library research methods. Using data analysis techniques in the form of reading and recording techniques. The results of this study show that the differentiated approach consists of three aspects, namely content differentiation, process differentiation, and product differentiation. 1) Content differentiation includes what students learn. In this regard, teachers modify the curriculum and teaching materials based on the learning styles and disability proceedings possessed by students. The content of the curriculum is adjusted to the circumstances and abilities of the students. 2) Process differentiation is the way students process and process ideas and information. How students interact with the material and how that interaction becomes a part that then determines student learning choices. Due to the many learning styles and differences in learning style choices presented by students, the class must be modified to accommodate different learning needs. 3) Product differentiation is how students demonstrate what they have learned. Learning products allow teachers to assess what material has been mastered by students and then present the next material. Student learning styles can also determine what student learning outcomes will be shown to the teacher.